Youth Perceptions of a Television Edutainment Program in Maintaining Standard Swahili in Tanzania - Beatrice Rabachi; Kaanaeli Kaale; Peter C. Mataba (Technium Social Sciences Journal, 2025)
Purpose: This study assessed the perceptions of youth in Mwanza City, Tanzania, regarding Star Television’s Kamusi ya Mtaa program and its role in maintaining standard Swahili. The research sought to examine the program’s content, analyze youth perceptions of its relevance, and evaluate its influence on their linguistic attitudes and practices. Methodology A convergent parallel mixed-methods design was employed. Quantitative data were collected from 80 youth (aged 15-35) via structured questionnaires, while qualitative data were gathered through focus group discussions, in-depth interviews with Swahili teachers and media producers, and a documentary review of program episodes. Quantitative data were analyzed using descriptive statistics with SPSS, and qualitative data underwent thematic analysis. Findings: The study revealed that Kamusi ya Mtaa primarily focuses on explaining street slang, reinforcing correct grammar, and promoting Swahili cultural identity. Youth perceived the program as highly educational and entertaining, with 81.3% reporting learning new Swahili words, 68.8% gaining confidence in using standard Swahili, and 60% consciously reducing their use of slang. The program was seen to reshape the prestige of standard Swahili, making it appear modern and desirable. However, limited digital accessibility and inconsistent broadcast schedules were identified as significant constraints to its reach and impact. Unique Contribution to Theory, Policy, and Practice: The study empirically validates Social Cognitive Theory in a linguistic context, demonstrating how media serves as a modeling tool for language behavior. It contributes to policy by highlighting the underutilized potential of edutainment media as a complementary tool to formal language policy for national language promotion. For practice, it provides broadcasters and language institutions with evidence-based strategies for designing effective, youth-centric language content.